Pengaruh Aktivitas dan Persepsi Pengunjung terhadap Sense of Place Ruang Publik (Kasus: Lapangan Gasibu) - Nadella, Audiza; Kusuma, Hanson Endra (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2024)
Environmental characteristics, visitor activities, and user impressions (sense of place) of Gasibu Park determine users' interest and the sustainability of Gasibu Park as a public space. This research aims to reveal user perceptions of the environmental characteristics, activities, and users’ sense of place, as well as the relationship between the three. This research used a mixed-method approach. First, text data from reviews on Google Maps was collected and analysed to explore user perceptions. Second, data was collected through an online questionnaire with closed-ended questions. The collected data was analysed using factor analysis to obtain dimensions of perception to the environmental characteristics, activity, and sense of place. From the multivariate regression analysis, it was revealed that the dimensions of environmental quality, location and accessibility, and management influenced the dimensions of suitability for the place, while the dimensions of management, public facilities, photography, and recreational tourism influenced the dimensions of dedication to place.